Extraction and Characterization of Bioactive Compounds in Horseradish (Armoracia rusticana): Focus on Polyphenols, Vitamin C, and Fatty Acids - Bianca Șuian; Sonia Amariei (Applied Sciences, 2025)
Horseradish (Armoracia rusticana) is a plant with a long tradition of use and numerous remarkable properties. It is especially appreciated for its antioxidant, antimicrobial, and anti-inflammatory effects. The therapeutic potential of the subject in the management of allergies has received comparatively less attention, despite its composition being rich in bioactive substances. The purpose of this research was to enhance the recovery of bioactive compounds from horseradish by applying an optimized ultrasound-assisted extraction process modelled through Design-Expert software (version 11). Spectrophotometric and chromatographic analyses revealed higher concentrations of polyphenols in extracts obtained with a methanol–water mixture (1:1, v/v) compared to ultrapure water, confirming the efficiency of solvents with lower polarity. The antioxidant activity was found to be significant, with the hydroalcoholic extract achieving 96.93% and the aqueous extract reaching 89.34%. The vitamin C content was determined to be 105.32 mg/100 g and 90.35 mg/100 g, respectively. The polyphenolic profile and fatty acid analysis confirmed the presence of bioactive compounds previously reported as antiallergenic, including protocatechuic, p-hydroxybenzoic, vanillic, caffeic, chlorogenic, p-coumaric, rosmarinic acids, and polyunsaturated fatty acids such as linoleic and linolenic acids, alongside the vitamin C content. The results of the present study confirm that horseradish is a rich natural source of bioactive compounds, particularly antioxidants, which may be of interest for further studies related to functional applications.